Dynamic magnetic‐coupling effect of two‐degrees‐of‐freedom direct drive induction motor. Issue 12 (10th September 2019) - Feng, Haichao; Si, Jikai; Wang, Peixin; Hua, Wei; Cheng, Zhiping; Li, Zhongwen
Abstract : The special structure of the two‐degrees‐of‐freedom direct drive induction motor (2DoFDDIM) gives rise to the magnetic‐coupling between the rotary and linear magnetic fields. In this article, the dynamic magnetic‐coupling effect, which is against the static coupling effect and indicates the special phenomenon caused by coupling magnetic fields in helical motion, is exposed and investigated based on the 3D finite‐element model (3D FEM). The control variable method is adopted and only the coupling magnetic field in helical motion is considered in this research. The performance changes caused by the dynamic magnetic‐coupling effect of the motor are simulated and analyzed. The relationship between the coupling magnetic field and the dynamic magnetic‐coupling effect is disclosed. To validate the 3D FEM and the magnetic‐coupling effect of 2DoFDDIM, a prototype and an experimental platform were built and measured. For the induced voltages caused by the magnetic‐coupling effect, the finite element analysis results are in agreement with the experimental results. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.